If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3y + -4(y + -2) = 10 Reorder the terms: 3y + -4(-2 + y) = 10 3y + (-2 * -4 + y * -4) = 10 3y + (8 + -4y) = 10 Reorder the terms: 8 + 3y + -4y = 10 Combine like terms: 3y + -4y = -1y 8 + -1y = 10 Solving 8 + -1y = 10 Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Add '-8' to each side of the equation. 8 + -8 + -1y = 10 + -8 Combine like terms: 8 + -8 = 0 0 + -1y = 10 + -8 -1y = 10 + -8 Combine like terms: 10 + -8 = 2 -1y = 2 Divide each side by '-1'. y = -2 Simplifying y = -2
| 6(j+35)=132 | | 9t-9+18T=6T+12 | | -1+19m=11m+23 | | lnx=.33 | | 5-2p=-3p-5 | | .75a+4=.25(3a-16) | | 0.7(3x+4)=1.1-(x+2) | | 4(9d+2)=2(d-17)-8d | | 0.2(x+10)+0.2x=6 | | 7y=2y+10-15 | | [21-5x]=33 | | -2(5s-6)-12=-29(8s+8)-3 | | 5y-4=2y+20 | | 2z+4=5z | | 2+5(2+5)= | | 5x=12-32+x | | 4+9lnx=7 | | 7n-4=n+1 | | 3s+5(s+7)=99 | | x^2+8x+16=99 | | 114-d=83 | | 2*16= | | -4.6b=28.106 | | x-2x+20=12 | | -3=-6t-3 | | Y=20-6x | | -12.5+0.5p=0.9p+5.3 | | Y=x^2-17x+50 | | 139=3d+2(4d+9) | | 3r=-21 | | 32-2x=20 | | 0=-16t^2+38.8t+3 |